THE APPLICATION OF HYDROTROPES AS MEDIUM IN THE EXTRACTION OF ANDROGRAPHOLIDE - Hartati, Indah; Kurniasari, Laeli; Anas, Yance; Aniq, Nur (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Hydrotrope solutions provide safe and effective media for the microwave assisted extraction of andrographolide, the major bioactive chemical constituent of plant Andrographis paniculata. Microwave assisted extraction of androgpaholide was carried out by using hydrotropes, sodium benzoate and urea. The objective of this work were to determine the Minimum Hydrotrope Concentration (MHC) and to determine the effectiveness of each hydrotrope with respect to andrographolide at different system powers. The microwave assisted extractions of andrographolide were carried out at different concentration of hydrotropes (0.2-3M) and different system powers (39.9 and 119.7 Watt). Twenty grams of Andrographis paniculata dried powder were added to 200 ml of hydrotrope solutions and extracted in a microwave extractor for 15 minutes. The research result showed that the percentage of the microwave assisted extraction of andrographolide by using sodium benzoate and urea were up to 10.9% and 1.05% respectively. The Minimum Hydrotrope Concentration and the effectiveness of hydrotropes that was measured in term of Setschenow constant (Ks) were reported for two hydrotropes used in this study.Â